Evidence of the Human Granulocytic Ehrlichiosis Agent in Ixodes ricinus Ticks in Switzerland - Pusterla, Nicola (American Society for Microbiology, 1999)
A total of 1,667 Ixodes ricinus ticks were collected from five regions in Switzerland where there have been sporadic occurrences of granulocytic ehrlichiosis in dogs and horses. The ticks were examined for rickettsiae of the Ehrlichia phagocytophila group via nested PCR. Twenty-one ticks (1.3%) were positive; 3 (0.5%) were nymphs, 6 (1.3%) were adult males, and 12 (1.9%) were adult females. The number of positive ticks varied with the stage of development and with the geographical origin. Nucleotide sequencing of the isolated PCR products identified these products as part of the 16S rRNA gene of Ehrlichia. In addition, these products had 100% homology with the agent of human granulocytic ehrlichiosis. The occurrence of this agent in I. ricinus in Switzerland presents a potential danger of transmission of granulocytic ehrlichiosis to dogs, horses, and humans.